2010
DOI: 10.1007/s00284-010-9713-3
|View full text |Cite
|
Sign up to set email alerts
|

Biosorption of an Azo Dye by Aspergillus niger and Trichoderma sp. Fungal Biomasses

Abstract: Biosorption is an eco-friendly and cost-effective method for treating the dye house effluents. Aspergillus niger and Trichoderma sp. were cultivated in bulk and biomasses used as biosorbents for the biosorption of an azo dye Orange G. Batch biosorption studies were performed for the removal of Orange G from aqueous solutions by varying the parameters like initial aqueous phase pH, biomass dosage, and initial dye concentration. It was found that the maximum biosorption was occurred at pH 2. Experimental data we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(10 citation statements)
references
References 16 publications
1
8
0
1
Order By: Relevance
“…Therefore, the use of bioremediation over physical and chemical procedures is a more efficient and economical way to remove colorants in wastewater. The ability of bacteria [4], fungi [5], and the other biological materials to decolorization dye especially Remozal Red dye has been successfully investigated [6]. Determination of optimum process conditions (pH of solution, biosorbent dosage, agitation period, temperature etc.)…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the use of bioremediation over physical and chemical procedures is a more efficient and economical way to remove colorants in wastewater. The ability of bacteria [4], fungi [5], and the other biological materials to decolorization dye especially Remozal Red dye has been successfully investigated [6]. Determination of optimum process conditions (pH of solution, biosorbent dosage, agitation period, temperature etc.)…”
Section: Introductionmentioning
confidence: 99%
“…Some recent decolorization studies carried out on model and industrial dyes have shown the biosorption activity of living and dead biomass of several Ascomycetes and Deuteromycetes, among which some specie belonging to the genus Aspergillus , with A. ochraceus and A. niger among the most effective . To the best of our knowledge, until now A. nidulans was never reported to be able to efficiently decolorize textile dyes, although its properties as biosorbent have already been shown for the removal of very dangerous pollutants from wastewaters, such as endosulfan and arsenic .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the results coming from the toxicity studies carried out on D. magna were very supportive for the future industrial application of A. nidulans, which was able to bring the toxicity of treated effluent A and C to naught from the fifth and the second day onwards, respectively. Some recent decolorization studies carried out on model and industrial dyes have shown the biosorption activity of living and dead biomass of several Ascomycetes and Deuteromycetes, among which some specie belonging to the genus Aspergillus, with A. ochraceus and A. niger among the most effective [25,49,76,[82][83][84]. To the best of our knowledge, until now A. nidulans was never reported to be able to efficiently decolorize textile dyes, although its properties as biosorbent have already been shown for the removal of very dangerous pollutants from wastewaters, such as endosulfan [85] and arsenic [86].…”
Section: Discussionmentioning
confidence: 99%
“…The experiments were carried out in a set of Erlenmeyer flasks (250 mL) by shaking desired amount of biosorbent powder in 100 mL Cr (VI) solutions as potassium dichromate (K 2 Cr 2 O 7) of desired concentrations, pH, and temperature to reach equilibrium of the solid-solution mixture. Samples were pelletized in a centrifuge at 10,000 × g for 5 min and the supernatants were essayed for residual Cr (VI) concentration by 1, 5-diphenylcarbazide spectrophotometric method (DPC) measuring the absorbance at 540 nm by using a spectrophotometer (WFZ800-D3B UV/VIS spectrophotometer) [13].…”
Section: Effects Of Biosorption Conditionsmentioning
confidence: 99%